COMPUTATIONAL SIMULATION OF A SYSTEM THERMOELASTICITY USING PYTHON - Luyo Sánchez, José (2011)
In this work, we present the development of a numerical scheme based in finite differences for numerical approximation to the solution of a unidimensional coupled linear thermoelastic system. Development the necessaries conditions for stability, consistence and convergence of the numerical scheme. Based in Von Neumann's method, we get the conditions for conditional stability of this algorithm and based in an example we contrast computationally the approximate the approximate solution got, by the finite differences scheme with the analytic solution.